1979
DOI: 10.1111/j.1365-2621.1979.tb06417.x
|View full text |Cite
|
Sign up to set email alerts
|

MlCROSTRUCTURE OF ISOLATED SOY PROTEIN IN COMBINATION HAM

Abstract: Combination hams were prepared by injecting excised porcine muscles with a brine containing solubilized isolated soy protein. The microstructure of the muscle in the combination ham was compared to that of a water added ham to determine the location of the isolated soy protein. The effect of ma&aging on the location of the isolated soy protein was also studied. The results showed that the isolated soy protein occupied primarily perimysial spaces and the massaging acts to incorporate these proteins into the end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1982
1982
1996
1996

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…This binding of water promotes the binding of meat pieces by minimizing the effect of excess water on the func tionality of the extracted myofibrillar proteins. Siegel et al (1979b) compared the microstructure of combina tion ham and water added to determine the location of the iso lated soy protein. The results showed that isolated soy protein fills primarily the perimysial spaces, but mechanical action by means of massaging or tumbling incorporates those proteins into the endomysial spaces and mixes them with the extracted myofibrillar proteins.…”
Section: Whole Muscle Extended Productsmentioning
confidence: 99%
“…This binding of water promotes the binding of meat pieces by minimizing the effect of excess water on the func tionality of the extracted myofibrillar proteins. Siegel et al (1979b) compared the microstructure of combina tion ham and water added to determine the location of the iso lated soy protein. The results showed that isolated soy protein fills primarily the perimysial spaces, but mechanical action by means of massaging or tumbling incorporates those proteins into the endomysial spaces and mixes them with the extracted myofibrillar proteins.…”
Section: Whole Muscle Extended Productsmentioning
confidence: 99%